Improving the Mechanisms of Digital Transformation of the Banking System of Uzbekistan under Conditions of Financial Globalization (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The digital transformation of the banking system has become a strategic priority in the context of financial globalization. In Uzbekistan, this process is not only a technological necessity but also a key driver of competitiveness in the financial sector. The integration of advanced digital solutions into banking operations improves efficiency, transparency, and customer accessibility. Global experience shows that countries actively implementing digital transformation achieve faster financial inclusion and higher economic resilience. However, the process requires careful planning, infrastructure development, and strong regulatory support. Therefore, studying the mechanisms for improving digital transformation in the banking system is both scientifically and practically relevant